2012
DOI: 10.1007/s13205-012-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-induced modulation of growth and antioxidant activity in the callus cultures of miswak (Salvadora persica)

Abstract: Miswak (Salvadora persica Linn.) is a medium-sized tree, desert facultative halophytic plant. Besides edible fruits and non-edible seed oil, the plant contains several bioactive compounds like alkaloids, tannins, saponins and sterols related to food and cosmetic industries. In the present study, physiological responses and antioxidant potential under salinity stress were investigated in callus cultures of S. persica to evaluate its use as a source of antioxidant. The callus cultures were grown on MS medium sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
5
14
0
Order By: Relevance
“…These results could be explained by the fact that salinity stress may be associated with an increase in secondary metabolites. Similarly, our previous study also suggested elevated antioxidant potentials under salt stress in callus culture of Salvadora persica (Sharma & Ramawat 2013).…”
Section: Discussionsupporting
confidence: 69%
“…These results could be explained by the fact that salinity stress may be associated with an increase in secondary metabolites. Similarly, our previous study also suggested elevated antioxidant potentials under salt stress in callus culture of Salvadora persica (Sharma & Ramawat 2013).…”
Section: Discussionsupporting
confidence: 69%
“…9). The results demonstrated a linear relationship between the inhibition percentage and extract concentration in agreement with the literature [64]. This small IC 50 reflects the high antiradical activity, which can be attributed to the presence of high levels of phenols and flavonoids in the extract [65].…”
Section: Antiradical Activity Of P Dactylifera L Extractsupporting
confidence: 89%
“…Plants cells have non-enzymatic and enzymatic defense system to control over production of ROS. Activity of antioxidant enzymes correlated with concentration of salt and plants spices (Sharma and Ramawat, 2013). Generally, during oxidative stress, plants with high antioxidant enzyme activity indicated better resistance to stresses (Parida and Das, 2005).…”
Section: Introductionmentioning
confidence: 93%